GG Cyber Cafe / Khairul Nizam Masri... [et al.] - Masri, Khairul Nizam; George, Adrian Walter; Muhd Fuad, Muhd Fareed; Ruslin, Razdey; Rider, Byron (2013)
The full service of GG cyber cafe establishment described in this business plan is a start up venture created by a group of determined and dedicated partners who loves to play computer games. These 5 partners has By focusing on high quality customer service, diverse offerings, creative promotion strategy and continuous development of employees, GG cyber cafe is projected to increase sales to more than RM 350,000 in three years while maintaining a high gross margin on sales while strengthening cash management and working capital. A comprehensive analysis of the market indicates that our cyber cafe is strong and robust, generating more than RM300000 in annual revenues. With technology advancement that occur, this industry or business sustains its durability and growth by offering high speed internet connection which benefits all of us. Additionally, GG cyber cafe are gathering more popularity due to the calm and joyful environment while having fun on serving internet and playing computer games that counteracting the high stress activities of daily life. The location of our cyber cafe is highly desirable as it is based at the centre of busy are which is 1Borneo, Sabah. Within the region, there are villagers and universities and also college that can come to our cyber cafe. Our chosen target markets which include 60% from university students, 20% from nearby residents, 15% from workers of 1B orneo and 5% from others categories. A review of our competitors shows that we will be competing against three other establishments in a ten-mile radius of our location. These businesses focus on same target market, pricing structures, and different in marketing approaches. With our consistent, high quality services and moderate pricing, we have the edge in attracting consumers location. Our concrete marketing plan will distinguish us as a GG cyber cafe of choice for customers. In planning for our launch, we have to put together a financial plan based on forecasts for the first three years of operations including our start-up expenses estimated RM156655. We will acquire a loan amount of RM56655. Each partner will contribute RM100000 to meet start up requirements. For our GG cyber cafe, we will generate sales revenue by offering high speed internet connection and various of LAN and internet computer games. During the first year of operations, we aim to generate RM 378,860 in sales revenue. For the second year, we plan to increase our sales by 3% or RM390,226 and RM409737 in third year.